Institutions, policy and the labour market: The contribution of the old institutional economics - Ioannis Katselidis (Economic Thought, 2019)
This paper seeks to examine the relationship and the interaction between institutions, policy and the labour market in the light of the ideas of the first generation of institutional economists, who, in contrast to neoclassicals, conceived of the economy as a nexus of institutions, underlining, therefore, the significant role of institutional and non-market factors in the functioning of an economic system. They also criticised those who define (economic) welfare only in terms of efficiency and satisfaction of consumer interests; institutionalists instead focus on issues related to justice, human self-development and labourers' welfare. In addition, early institutionalists paid considerable attention to the institutional framework of the labour market. In particular, the first generation of institutional economists highlighted the importance of institutions and other non-market parameters in determining the level of wages and employment (e.g. the role of the bargaining power of workers and employers). Furthermore, they made substantial contributions towards the field of labour policy and they were pioneers in the formulation of economic and social policy. Specifically, various modern institutions and labour market policies, such as unemployment benefits, industrial training and active employment policies, were implemented in the US, during the first decades of the 20th century, after the recommendation of the institutional labour economists. Therefore, their ideas, besides being interesting from a historical point of view, may also be useful in today's analysis of workers' problems and the functioning of modern labour markets.
Keywords: B15; B25; J08; 330; Institutional School; History of Labour Economics; Labour Policy; Labour Market Institutions